Educational Research, Adisciplinarity, and the Study of Constitution - Hodgson, Naomi (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2024)
In response to considerable critique of its rigour and relevance, the field of educational research has sought to prove its validity, both in terms of its scientific legitimacy and its relevance to policy and practice. One result of this has been a heightened concern with methodology, to the extent that a form of methodolatry has developed. In conjunction with wider changes in the governance of research, from disciplinary to thematic foci, educational research seems also prone to adisciplinarity. Critiques from philosophy of education of the privileging of gold-standard methodologies point to the empiricism that characterises the field and how this can overlook questions of value and meaning. It is arguably not the empiricism as such that is problematic, but its unmooring from the theoretical and the educational. The possibility of an anthropologically informed educational philosophy is explored as a way out of the impasse.